Interval Training and Endurance Training to Increase VO2max: Article Review - Fajar Syamsudin; Rony Syaifullah; Muhammad Bakhtiar Subardi; Sayid Fariz (JUARA : Jurnal Olahraga, 2021)
This study aims to determine better between Interval Training and Endurance Training to increase VO2max capacity in healthy adult men and women. The method used is a literature review, looking for articles from Electronic DataBased in PubMed, ScienceDirect, Eric. Journal, Google Scholar, and ProQuest that have been published and accredited. A total of 8 papers were selected for in-depth review. The results show that Interval Training is better than Endurance Training, even though both can increase VO2max.